2007
DOI: 10.1038/sj.bjp.0707267
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutrophil elastase in LTB4‐induced neutrophil transmigration in vivo assessed with a specific inhibitor and neutrophil elastase deficient mice

Abstract: Background and purpose: The serine protease neutrophil elastase (NE) appears to regulate inflammatory responses at multiple levels but its role in leukocyte transmigration in vivo remains unclear. The present study aimed to address this issue by using both an NE inhibitor (ONO-5046) and NE deficient (NEExperimental approach: A number of inflammatory mediators (LTB 4 , KC and PAF) were investigated in vitro for their ability to stimulate the release and the surface expression of NE by neutrophils. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
2
60
0
1
Order By: Relevance
“…N-methoxysuccinyl-Ala-Ala-Pro-Val p-nitroaniline (Sigma Chemical) was used as the substrate for neutrophil elastase (NE), as this compound is not hydrolyzed by cathepsin G. Hydrolysis of the substrate by NE was determined spectrophotometrically at 405 nm. In brief, 1 mM substrate was incubated with 0.2 ml of sample in 0.1 M Tris (hydroxyl-methyl) aminomethane-HCl buffer (pH 8.0) containing 0.5 M NaCl at 37°C for 24 h. Optical density was determined and activity of NE was determined, where one enzyme unit is defined as the quantity of enzyme that liberated 1 mol of p-nitroaniline in 24 h (65).…”
Section: Intratracheal (It) Instillationsmentioning
confidence: 99%
“…N-methoxysuccinyl-Ala-Ala-Pro-Val p-nitroaniline (Sigma Chemical) was used as the substrate for neutrophil elastase (NE), as this compound is not hydrolyzed by cathepsin G. Hydrolysis of the substrate by NE was determined spectrophotometrically at 405 nm. In brief, 1 mM substrate was incubated with 0.2 ml of sample in 0.1 M Tris (hydroxyl-methyl) aminomethane-HCl buffer (pH 8.0) containing 0.5 M NaCl at 37°C for 24 h. Optical density was determined and activity of NE was determined, where one enzyme unit is defined as the quantity of enzyme that liberated 1 mol of p-nitroaniline in 24 h (65).…”
Section: Intratracheal (It) Instillationsmentioning
confidence: 99%
“…A direct cleavage assay using purified, functionally active CD11b/CD18 further confirmed the specific cleavage of CD11b by neutrophil serprocidins (Figures 5-6). The finding that NE, NCG and NPR-3 can all contribute to CD11b shedding and PMN detachment may also provide clues that explain the controversial reports [18][19][20][22][23][24][25][26] on the roles of serprocidins in modulating PMN recruitment. Because each of the 3 serprocidins can effectively cleave CD11b, the combination of NE, NPR-3, and NCG forms a highly efficient mechanism for the rapid shedding of neutrophil CD11b during cell detachment and subsequent migration.…”
Section: The Role Of Leukocyte Serprocidins In Modulating Cd11b Sheddmentioning
confidence: 91%
“…Using NE-deficient mice and various inflammatory mouse models, systematic studies from Nourshargh's laboratory demonstrated the essential role of NE in mediating PMN transmigration. 19,20,22 In contrast, Hirche et al 23 reported no significant defects of leukocyte transmigration in mice with individual NE knockouts. Similarly, the inhibition of NE by a specific inhibitor did not affect leukocyte transendothelial migration under flow.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…First recognized as degradative enzymes able to kill pathogens and cleave extracellular matrix components, NSPs have been attributed a potential role in chemotaxis and migration through cleavage of adhesion molecules at intercellular junctions (Cepinskas et al, 1999;Hermant et al, 2003). This function, however, remains debated because some studies demonstrated decreased neutrophil chemotaxis when using NSP inhibitors (Stockley et al, 1990;Lomas et al, 1995;Young et al, 2007), whereas others have revealed no alteration of neutrophil migration in response to neutrophil-specific chemotactic stimuli in animal models deficient in NSPs (MacIvor et al, 1999;Adkison et al, 2002;Allport et al, 2002).…”
Section: Biological Functions Of Elastase Proteinasementioning
confidence: 99%